STRATEGI PROMOSI DALAM MENINGKATKAN PENJUALAN LUSCIOUS CHOCOLATE POTATO SNACK - Marceline Livia Hedynata; Wirawan Endro Dwi Radianto (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2016)
So far, promotion strategies which used by LUSCIOUS Chocolate Potato Snack to promote and sell products was not maximal that caused the company's sales target (sales force) problem that has not been achieved and customer coverage is still narrow. The purpose of this research is to determine the promotional strategies that can increase product sales of LUSCIOUS Chocolate Potato Snack. This type of research is using qualitative with case study method. Data retrieval technique is using purposive sampling method. Data collection techniques using semi-structured interviews by involving 12 informants, consist of 5 consumers, 2 agents personal reseller, 2 owner of the company as an agent of a distributor, and 3 marketing expert. The collection of data is also supported by documentation in the form of photographs with informants and internal data firm. Validity and reliability of this research using triangulation source method. Technical analysis of the data in this research consists of three stages: data reduction, data presentation, and conclusion. The results showed that LUSCIOUS Chocolate Potato Snack need of repair and upgrading basic campaign strategy in 8 models of the promotional mix. There are 5 models of promotional mix was chosen as the focus of LUSCIOUS’ improvement promotional strategies which still in startup business, namely Events and Experiences, Direct Marketing, Sales Promotion, Interactive Online Marketing, and Word of Mouth Marketing. As for the third promotion mix, namely, Personal Selling, Public Relations and Publicity, and Advertising, is not become the focus of LUSCIOUS’ promotional strategies.